2022
DOI: 10.3390/ijerph191710614
|View full text |Cite
|
Sign up to set email alerts
|

Digital Transformation on Enterprise Green Innovation: Effect and Transmission Mechanism

Abstract: With the development of blockchain, big data, cloud computing and other new technologies, how to achieve innovative development and green sustainable development in digital transformation has become one of the key issues for enterprises to obtain and maintain core competitiveness. However, little of the literature has paid attention to the impact of digital transformation on enterprise green innovation. Using the data of Chinese A-share listed companies from 2010 to 2020, this paper empirically analyzes the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 107 publications
2
34
0
Order By: Relevance
“…The essence is to apply digitalization to the strategic layer of the enterprise, to promote the reform of the organizational structure and management methods of the enterprise, and to enhance the core competitiveness of the enterprise through endogenous and external growth. Feng et al (2022) defined digitization as the transformation of organizations that integrate mathematical techniques and business processes into the digital economy [ 18 ]. Shpak et al (2020) defined digital transformation as the use of technology to radically improve business performance or reach [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…The essence is to apply digitalization to the strategic layer of the enterprise, to promote the reform of the organizational structure and management methods of the enterprise, and to enhance the core competitiveness of the enterprise through endogenous and external growth. Feng et al (2022) defined digitization as the transformation of organizations that integrate mathematical techniques and business processes into the digital economy [ 18 ]. Shpak et al (2020) defined digital transformation as the use of technology to radically improve business performance or reach [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Scholars usually use input-output tables or macroeconomic indicators to measure the level of digital economic development including national, provincial and urban dimensions (Balcerzak and Pietrzak, 2017;Liu et al, 2022;Zhang C et al, 2022). Or use text analysis to measure the degree of digital transformation at the enterprise level (Feng et al, 2022), and a small number of studies have measured the degree of digital transformation at the industry level. These studies can reflect the development of digital economy or digital transformation in China to some extent.…”
Section: Digital Transformationmentioning
confidence: 99%
“…Roh et al [41] used data from South Korea's manufacturing industry from 2014 to 2016 and found that corporate intellectual property significantly affects green product innovation. Feng et al [42] found that digital transformation promotes green innovation in Chinese enterprises by constructing a double-fixed-effect model. Liu [43] constructed the short-sighted indicators of managers through text analysis and machine learning and found that the short-sighted behavior of management is negatively correlated with corporate green innovation.…”
Section: Enterprise Green Innovationmentioning
confidence: 99%